Evolution of TiO2 Nanotubular Morphology Obtained in Ethylene Glycol/Glycerol Mixture and its Photoelectrochemical Performance - Bervian,Alexander (2017)
The evolution of TiO2 nanotubular morphology, synthesized in a mixture of fluorinated ethylene glycol and glycerol electrolyte, was studied as a function of the anodization time. The samples were characterized by FEG-SEM, XRD, XPS, UV-Vis and EIS. The formation of single-or double-walled TiO2 nanotube structure can be efficiently controlled by the anodization time. For anodization times less than 30 minutes, a compact oxide layer is formed, followed by double-walled nanotube formation up to 120 minutes and single-walled nanotubes up to 240 minutes. XPS analyses show that the samples obtained with short anodization time have a high carbon content and oxygenated surface species compared to the longer-time anodized sample; however, binding energy peaks for Ti 2p remained invariant. The performances of TiO2 nanotubular photoelectrodes were evaluated in photoelectrochemical water splitting where TiO2 nanotubes anodized for 120 minutes presented the best performance that was related to their optimal morphology and charge transportation.